Systematic Review of Solar and Wind Power Plants for 14-Meter Fishing Boats - Nanang Setiyobudi; Agoes Santoso; Eddy Setyo Koenhardono; Achmad Baidowi; Dian Purnamasari; Teguh Muttaqie; Muryadin; Fariz Maulana Noor; Ari Budi Setiawan; Ari Kuncoro; Zarochman (International Journal of Marine Engineering Innovation and Research, 2023)
The use of fossil fuels is becoming increasingly expensive, and the amount is limited. Utilizing wind and solar energy sources onboard fishing vessels during operation is one of the solutions to reduce operational costs. This article presents a study on applying solar photovoltaic (PV) and wind turbines for a 14-meter BSC (Blue Swimming Crab) fishing vessel in Rembang Regency, Indonesia. This study discusses the use of renewable energy sources that can be applied to meet onboard electricity needs and their economic impact. This analysis considers to operating system scenario for seven days catching the BSC in the Java Sea. The calculation results show that the solar PV and wind turbine energy that can be utilized as electrical energy are 22,960-Watt h. The required battery is 20 units at 100 Ah 12 Volts and an investment cost of USD 21,084. The advantage of applying this technology is an operational cost saving of 16%, which can increase fishermen’s income by 11%. The challenge of a hybrid or electric propulsion system is fantastic, using the serial configuration of the power topology, and the result of preliminary estimates of the investment value is approximately 173,277 USD.